The maintenance of long-term weight loss after semaglutide withdrawal in obese women with PCOS treated with metformin: a 2-year observational study - Jensterle, Mojca; Ferjan, Simona; Janez, Andrej (Frontiers in Endocrinology, 2024)
Background: Withdrawal of semaglutide is frequently followed by weight regain due to compensatory biological changes that prevent the maintenance of long-term weight loss. There are some studies implying that metformin might attenuate weight regain. The weight trajectory after discontinuation of short-term semaglutide treatment in obese women with PCOS who continued metformin treatment has not yet been evaluated.We explored changes in body weight, cardiometabolic and endocrine parameters in obese women with PCOS who continued treatment with metformin 2 years after discontinuation of short-term intervention with semaglutide.Methods: 25 women with PCOS and obesity, aged 33.7 ± 5.3 years (mean ± SD), were treated with once-weekly subcutaneous semaglutide 1.0 mg as an adjunct to metformin 2000 mg/day and lifestyle intervention for 16 weeks. At week 16, semaglutide was discontinued. Treatment with metformin 2000 mg/day and promotion of lifestyle intervention were continued during the 2-year follow-up period. Weight change, cardiometabolic, and endocrine parameters were assessed 2 years after semaglutide discontinuation.Results: During semaglutide treatment phase, weight decreased from 101 (90-106.8) kg to 92 (83.3-100.8) kg. Two years after semaglutide withdrawal, weight was 95 (77-104) kg. The net weight loss 2 years after discontinuation of semaglutide remained significant when compared to baseline (p=0.003). At the end of the study, 21 out of 25 subjects had lower body weight compared to baseline. Improvements in cardiometabolic parameters including decrease in total and LDL cholesterol, fasting glucose, and glucose after OGTT that had been seen during semaglutidetreatment phase reverted towards baseline two years after semaglutide cessation. Free testosterone levels significantly decreased during semaglutide treatment from 6.16 (4.07-9.71) to 4.12 (2.98-6.93) nmol/l, (p= 0.012) and did not significantly deteriorate after semaglutide discontinuation.Two years after semaglutide withdrawal, women with PCOS who continued with metformin regained about one-third of the semaglutide-induced weight loss. At the end of the follow up, 84% of women had a lower body weight than at baseline.